Anioły w interpretacji teoretycznej i w odniesieniach ascetycznych św. Hieronima w świetle jego "Homilii o Psalmach" - Turek, Waldemar Jan (Vox Patrum, 2025)
The author of the article analyses selected fragments from the Homilies on the Psalms of St. Jerome, in which the great exegete takes up, based on the relevant biblical texts, the topic of angels and their attitudes. St. Jerome presents us, on the one hand, the activity of angels serving God and placed on an equal footing with martyrs and monks, and on the other hand he describes the fallen angels who distanced themselves from God through their sin of pride, wanting to be equal to God himself. The article shows in a very concrete way how St. Jerome moves from theoretical exegetical explanations to practical ascetic references. The attitude of angels, servants of God, can be an example for monks and all Christians, while the fall of angels who distanced themselves from God is a warning to all believers in Christ.